2019
DOI: 10.1136/bmjsem-2019-000560
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of almond, dried grape and dried cranberry consumption on endurance exercise performance, recovery and psychomotor speed: protocol of a randomised controlled trial

Abstract: BackgroundFoods rich in nutrients, such as nitrate, nitrite, L-arginine and polyphenols, can promote the synthesis of nitric oxide (NO), which may induce ergogenic effects on endurance exercise performance. Thus, consuming foods rich in these components, such as almonds, dried grapes and dried cranberries (AGC), may improve athletic performance. Additionally, the antioxidant properties of these foods may reduce oxidative damage induced by intense exercise, thus improving recovery and reducing fatigue from stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Among them, the intake of phenolic compounds appears to be a beneficial strategy thanks to their ability to suppress inflammation by inhibiting oxidative damage and interacting with the immune system, and in this way, recover muscle strength and soreness, reduce fatigue and cellular damage, and preserve myocytes (Figure 5) [105,115]. In addition, they can also contribute to improving physical performance, endurance, recovery, and cardiovascular function during exercise, as well as contributing to better psychological and physiological conditions of the athletic community [114,116]. Even so, and although some experts alert that excessive amounts of phenolics can be dangerous given the absence of studies and long-term health benefits, dietary supplementation of botanical origin is increasing worldwide, which is not surprising considering their nature and medicinal use since ancient times in folk medicine [117].…”
Section: Effects Of Phenolic Compounds and Phenolic-rich Sources On E...mentioning
confidence: 99%
“…Among them, the intake of phenolic compounds appears to be a beneficial strategy thanks to their ability to suppress inflammation by inhibiting oxidative damage and interacting with the immune system, and in this way, recover muscle strength and soreness, reduce fatigue and cellular damage, and preserve myocytes (Figure 5) [105,115]. In addition, they can also contribute to improving physical performance, endurance, recovery, and cardiovascular function during exercise, as well as contributing to better psychological and physiological conditions of the athletic community [114,116]. Even so, and although some experts alert that excessive amounts of phenolics can be dangerous given the absence of studies and long-term health benefits, dietary supplementation of botanical origin is increasing worldwide, which is not surprising considering their nature and medicinal use since ancient times in folk medicine [117].…”
Section: Effects Of Phenolic Compounds and Phenolic-rich Sources On E...mentioning
confidence: 99%
“… Blood and urine samples before and after 30 days (fasting > 10 h) ↑ ORAC at day 30; ↓ FRAP value in the placebo group but not in the test group; ↑ urinary isoprostane values in the placebo group but not in the test group; ↓CK ↑ hemoglobin levels in the test group; no differences in the effort test; differences in physical performance among sport disciplines Skarpańska-Stejnborn, Basta, Pilaczyńska-Szcześniak, & Horoszkiewicz-Hassan, 2010 [ 89 ] Grape derived product containing black wine grape peel and seed extract One capsule contains 188 mg/g of polyphenols (catechin, gallic acid, quercetin, trans-resveratrol, cis-resveratrol) and 35 mg/g of anthocyans (malvidin, peomidin, petunidin, delphinidin, cyanidin) One gelatin capsule/day of 367 mg for 6 weeks Trained male rowers ( n = 22) Physical exercise test on the rowing ergometer; varying between 40 and 90% of maximal aerobic power Blood sample before, 1 min after the test completion and after 24 h ↑ TAC; insignificant increase in SOD; ↓ GPX; ↓lipid peroxidation product levels Taghizadeh, Malekian, Memarzadeh, Mohammadi, & Asemi, 2016 [ 90 ] Grape seed extract No info 300 mg twice a day for 8 weeks Female volleyball players ( n = 40) No specific test Blood before and after. Fasting 12 h ↑ GSH; ↓ MDA; ↓ insulin; ↓ homeostasis model of assessment for insulin resistance (HOMA-IR); ↑ insulin sensitivity check index (QUICKI); no significant effects on CK; TAC; NO; FPG and lipid concentrations Cases et al, 2017 [ 92 ] An innovative polyphenol-based food supplement Bioactives 410 mg/1000 mg; Polyphenolic bioactives 290 mg/1000 mg; Caffeine 120 mg/100 mg 2 capsules of 500 mg, 60 min before the exercise protocol Recreationally active male athletes ( n = 15) The Wingate test Blood before, after and at recovery period ↑ oxidative homeostasis; ↑SOD; ↑GSH; ↑CAT; ↑ total power output; ↑ maximal peak power output; ↑ average power developed; ↔ fatigue; ↔ heart rate; ↑ oxidative homeostasis D’unienville et al, 2019 [ 93 ] Dried grapes with almonds and dried cranberries One product mix contains 560.3 mg of total polyphenols; 14.84 mg of flavonoids One product mix/day (2550 KJ/day of energy) for 4 weeks (75 g of raw, natural, unsalted almonds + 25 g of dried grapes (sultanas) + 25 g of dried cranberries) Trained male cyclists/triathletes ( n = 96) Endurance exercise performance Blood and urine samples Results to be published VO2max maximal oxygen uptake, ...…”
Section: Introductionmentioning
confidence: 99%
“…Studies found with this type of supplements are focused on an extract obtained from the grape’ skin [ 88 ], extracts obtained from grape seeds [ 89 , 90 ], the whole grape [ 91 ], an innovative polyphenol-based food supplement based on a grape extract [ 92 ] and dried grapes with almonds and dried cranberries [ 93 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation